Influence Motivation Work, Leadership, And Discipline Work on Employee Performance of PT. Gama Global Tobako - Sopiyan Sopiyan; Asnawi Hidayat (Pusat Riset dan Inovasi Nasional, 2025)
Employee performance is a crucial factor that directly contributes to the achievement of company goals, but the evaluation process is often complex. This study aims to examine and evaluate the influence of work motivation, leadership, and work discipline on improving employee performance. The study used a descriptive quantitative method through a survey by distributing questionnaires to 87 employees of PT. Gama Tobako Karanganhyar. The data obtained were analyzed using multiple linear regression tests with the help of SPSS software version 29.1. The results of the analysis showed that the variables of work motivation, leadership, and work discipline had a significant effect on increasing employee performance productivity. Partially, work motivation is a dominant factor in driving productivity, with a regression coefficient value of 0.859, t-count of 5.544, and a significance level of 0.000. These findings indicate that the higher the motivation, both intrinsic and extrinsic, the greater the contribution to improving work quality, productivity, and employee commitment to the company.